Beauty Goes Green: Determinants of Sustainable Purchasing Behavior Among Gen X and Z Filipino Consumers - Nina Isabel Bautista; Jillian Shamira Palmiano; Alyanna Raiza Reyes; Ysabel Maria Louise San Juan; Antonio Jr. Etrata (MEC-J (Management and Economics Journal), 2023)
Several companies have adopted sustainability as a business approach to create long-term value by ensuring that they operate in an ethical way that protects the social, ecological, and economic environments. Nowadays, the demand for sustainable products has increased in various industries, including the cosmetics industry, and customers go through a complex process when deciding which products to buy. Hence, there is a lack of study in terms of determining the disparity between the purchasing behavior of Generation X and Z. With that, this study determined the specific difference between the purchasing behavior of Gen X and Z as green cosmetic product consumers and identified which among the factors; environmental consciousness, eco-label, attitude, green advertising and price sensitivity significantly influence their buying behavior as well as their perception towards them. An online questionnaire was distributed to 385 respondents, and the data gathered for this quantitative study were analyzed through descriptive statistics, t-test, and multiple linear regression. The findings of this study show that while all factors are perceived as important for both generations and have a role in their behavior as a consumer of green cosmetics products, only price sensitivity significantly affect the purchasing behavior of Gen X. On the other hand, both eco-label and price sensitivity significantly affects Gen Z’s purchasing behavior toward green cosmetic products.